Advanced electrochemical detection of arsenic using platinum-modified boron-doped diamond by anodic stripping voltammetry - Fatah, Fadhlir R. A. A.; Sitorus, Rinaldo; Saefumillah, Asep; Mubarok, Hanif; Pramadewandaru, Respati K. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Platinum-modified boron-doped diamond (BDD) electrodes were effectively fabricated through a combination of wet seeding and electrodeposition techniques. Methods: This research involved the utilization of various chemicals and apparatus, the modification of boron-doped diamond (BDD) electrodes with platinum using wet seeding and electrodeposition, and the detection of As3+ and As5+ using a phosphate buffer solution and anodic stripping voltammetry (ASV). Findings: Characterization using Scanning Electron Microscopy-Energy Dispersive Spectroscopy (SEM-EDS) confirmed the successful deposition of 1.54% platinum on the BDD surface. These modified electrodes were employed as sensors for arsenic species (As³⁺ and As⁵⁺) using anodic stripping voltammetry (ASV) in a 0.1 M phosphate buffer solution at pH 6. Under optimal conditions, including a deposition potential of -500 mV, a deposition time of 150 s, and a scan rate of 200 mV/s, the linear detection of As³⁺ and As⁵⁺ was achieved within a concentration range of 0 to 100 ppb (R² = 0.9797 and 0.9903, respectively). Prior to ASV detection of As⁵⁺, a pretreatment step involving the addition of 0.1 M NaBH₄ was necessary to reduce As⁵⁺ to As³⁺. The detection limits for As³⁺ and As⁵⁺ were determined to be 16.50 ppb and 8.19 ppb, respectively. Conclusion: This research highlights the potential of BDD/Pt electrodes in environmental monitoring and arsenic detection applications and demonstrates the method's efficacy for the speciation analysis of arsenic species. Novelty/Originality of this Study: This research pioneers the use of platinum-modified boron-doped diamond electrodes for the speciation analysis of arsenic, offering a promising new approach for environmental monitoring applications.